Manajemen Keuangan Swalayan Program di Mts Ponpes Modern Putri Ulul Albab Kecamatan Koto Baru Kabupaten Dharmasraya - Yanti, Yuli (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Sakinah Dharmasraya, 2021)
This research is conducted to study the self-service financial management program at MTs Ponpes Modern Putri Ulul Albab, Koto Baru Subdistrict, Dharmasraya Regency. The use of methods is carried out with qualitative research and is descriptive. Observation techniques, interview techno, and documentation techniques are used in data collection techniques. Analytical techniques use data triangulation that contains observations and interview results. The results of the research show that in the following explanation. First, the policy of planning money management in Pondok Pesantren Modern Putri Ulul Albab is by the standards of pesantren huts that all santriwati must collect money from the cooperative treasurer. Second, organizing the money use management policy in Pondok Pesantren Modern Putri Ulul Albab is by the standards of pesantren huts, namely in financial management. Third, implementing the policy of using money in Pondok Pesantren Modern Putri Ulul Albab has begun to be effective. Four, supervision of the use of money in Pondok Pesantren Modern Putri, Ulul Albab is following boarding school standards but needs to be improved again in the supervision of the management of the use of the money so that there are no more errors in financial management.